The structure of the first forty-five questions of the Summa theologiae of Saint Thomas Aquinas - Hankey, W; Hankey, Wayne J. (1982)
﻿ The thesis has four main parts. The introduction, "Contemporary Thomism", endeavours to justify a re-examination of the structure of the initial questions of the Summa Theologiae on account of the distortions in the presentation of Thomas inherent in the Leonine revival. The four chapters of Part Two consider first, Lombard's Sentences, second, Anselm's Monologion and Proslogion, third, Boethius' De Trinitate, the De Divinis Nominibus of Dionysius and the De Divisione Naturae of Eriugena, and fourth, the Neoplatonism of Proclus and Porphyry in a search for the origins of Thomas' theological structure. It concludes that for the specific features of his system Thomas reaches back beyond the Sentences to the pagan and Christian adaptations of the opposing traditions of Porphyry and Iamblichus. The five chapters of Part Three analyze the structure of the questions. The first chapter considers the place of the "five ways"; the other four treat questions 1 - 13; 14 - 26; 27 - 43; and 44 - 45 respectively. The analysis discovers a common circular structure in which there is a gradual development from the divine simplicity toward more inclusive and concrete forms of divine self-relation. It finds also an incompletely resolved tension between simplicity and self-relation which are drawn from the contrary Neoplatonic logics of infinite and finite. The thesis concludes that Thomas is better understood as part of the Neoplatonic development of systematic thought than from existentialist perspectives opposed to this tradition.